2010
DOI: 10.1111/j.1574-6968.2010.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel Staphylococcus pseudintermedius exfoliative toxin gene and its prevalence in isolates from canines with pyoderma and healthy dogs

Abstract: Staphylococcal exfoliative toxins are involved in some cutaneous infections in mammals by targeting desmoglein 1 (Dsg1), a desmosomal cell-cell adhesion molecule. Recently, an exfoliative toxin gene (exi) was identified in Staphylococcus pseudintermedius isolated from canine pyoderma. The aim of this study was to identify novel exfoliative toxin genes in S. pseudintermedius. Here, we describe a novel orf in the genome of S. pseudintermedius isolated from canine impetigo, whose deduced amino acid sequence was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
5
38
1
1
Order By: Relevance
“…46.6% (Lautz et al 2006), but almost equal to the percentage reported by Yoon et al (2010). The occurrence of the exi gene (22.8%) was similar to that observed by FutagawaSaito et al (2009) and the prevalence of the expB gene (7.6%) was lower than the 23% indicated by Iyori et al (2010). The prevalence of the enterotoxinrelated gene sec canine (16.5%) was close to the 12.6% reported by Becker et al (2001) but lower than the 24% described by Yoon et al (2010) and other authors who confirmed its presence in all tested isolates (Futagawa-Saito et al 2004).…”
Section: Discussionsupporting
confidence: 82%
“…46.6% (Lautz et al 2006), but almost equal to the percentage reported by Yoon et al (2010). The occurrence of the exi gene (22.8%) was similar to that observed by FutagawaSaito et al (2009) and the prevalence of the expB gene (7.6%) was lower than the 23% indicated by Iyori et al (2010). The prevalence of the enterotoxinrelated gene sec canine (16.5%) was close to the 12.6% reported by Becker et al (2001) but lower than the 24% described by Yoon et al (2010) and other authors who confirmed its presence in all tested isolates (Futagawa-Saito et al 2004).…”
Section: Discussionsupporting
confidence: 82%
“…1). Regarding the exfoliative toxins in MSSP reported on here, one human isolate yielded a positive PCR result for ExpA, while two canine strains were found positive for ExpB, indicating that these virulence factors may be more frequently associated with cases of superficial dermatitis in dogs [32], [33].…”
Section: Discussionmentioning
confidence: 56%
“…The presence of the exfoliative toxin ExpA (formerly named EXI) was determined by PCR with the primers exp A-F GCGCGTCCTTCTGATCCAGAACT and exp A-R AACGTCCCCCTTTACCTACGTGAAT (according to AB489850.1, [32] at an annealing temperature of 58°C (25 cycles) including strain IMT21652 (JN604832) as a positive control. Detection of the gene encoding ExpB was performed as described previously [33].…”
Section: Methodsmentioning
confidence: 99%
“…The authors proposed the renaming of EXI as EXPA (exfoliatin of S. pseudintermedius type A), and the novel protein was named EXPB (exfoliatin of S. pseudintermedius type B). Moreover, it was shown that both EXPA and EXPB could digest canine desmoglein-1 (Dsg-1) and caused subcorneal splits in the epidermis when injected in mice, which resembles mechanisms involved in the pathogenesis of intraepidermal splitting in canine impetigo (46,47).…”
Section: Staphylococcus Pseudintermediusmentioning
confidence: 99%